PENERAPAN ALGORITMA LEVENSTEIN PADA APLIKASI KOMPRESI FILE MP3 - Sari, Tetti Purnama; Nasution, Surya Darma; Hondro, Rivalri Kristianto (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2018)
Compressed files require less disk space than files that are not compressed, so compressing is useful for backing up data by using storage space to be small or to send information over the Internet faster. MP3 makes the audio format often used because the data stored resembles the original data when recorded and has a size that is not too large compared to other formats. Users besides storing song files, they also store videos and other files and users also want the highest quality data and minimum quantity (size). So to make a lot of empty space and have a size of data that is not large on storage media, a compression method that means to shorten the size of the bits needed for data is needed. Algorithms used in the compression process, including the Levenstein algorithm which is a type of lossless compression. Applying the Levenstein algorithm to the compression process the author wants to know the performance of compression when done by compressing MP3 files, so that large MP3 files will be compressed into smaller sizes, so that the transmission process is carried out faster and reduces the data storage location.Keywords: MP3, File, Levenstein